Andragogy-Based Writing Skills Training Model in Developing Critical Thinking Abilities - Haruman Taufik Kartanegara; Mustofa Kamil; Yanti Shantini; Joni Rahmat Pramudia; Asep Saepudin (Qalamuna)
This study aims to develop and measure the effectiveness of the andragogy-based writing skills model in improving the critical thinking skills of educators at SMAN 2 Cianjur. The training is designed as a transformation process, where educators are invited to realize their potential and habits in daily activities to build critical awareness. With the integration of technology in training, limited access to education and training in areas such as Cianjur can be overcome, expanding opportunities for digital literacy and collaboration between educators. A quantitative method with a quasi-experimental design was used in this study, where writing training was shown to improve teachers' writing and critical thinking skills. The trained teachers can produce articles, teaching materials, and documentation of good practices published on the Lentera Mahardika and PMM platforms. The study's results showed a significant improvement in writing skills and contribution to learning quality. This study emphasizes the importance of writing habits as a hobby for educators to strengthen innovation and relevance of education in the future.